The Association between Dietary Patterns and Chemotherapy Side Effects in Patients with Breast Cancer (BrCa). (16th March 2023) - Sanati, Vahid; Sohouli, Mohammad Hassan; Dareini, Homa; Esmailzadeh, Ahmad; Sajadian, Akram-Sadat; Raji Lahiji, Mahsa; Clark, Cain C. T.; Zarrati, Mitra
Abstract: This study aimed to determine the relationship between food pattern and dietary intake before and during chemotherapy with the severity of gastrointestinal side effects, cancer-related fatigue, and chemotherapy-induced pain. This study was performed on 204 patients with breast cancer who were undergoing chemotherapy. Dietary pattern was collected by food frequency questionnaire and dietary intake during chemotherapy using a 24-hour food recall questionnaire. The severity of chemotherapy side effects including nausea, vomiting, constipation, diarrhea, CRF, and pain was also assessed by valid questionnaires. The relationship between dietary pattern and mean score of chemotherapy side effects was calculated using linear regression analysis. Three dietary patterns were extracted from the participants. After adjusting the effect of all possible confounders, no significant relationship was found between the dietary pattern one year before the start of treatment and the mean of chemotherapy side effects severity. Although the mean of daily energy intake with the severity of nausea and vomiting (r = −0.258, P-value <0.01), constipation, fatigue, and pain have a significant inverse relationship. Nutrition education and following a healthy diet are needed to reduce the severity of chemotherapy side effects during this period.